Role of N-acetylcysteine treatment in women with advanced age undergoing IVF/ICSI cycles: A prospective study - Li, Xiufang; Wang, Zhongqing; Wang, Huidan; Xu, Haiyan; Sheng, Yan; Lian, Fang (Frontiers in Medicine, 2022)
Objective: The main objective of this study was explore the efficacy of a new antioxidant N-acetylcysteine(NAC)supplementation in reproductive outcomes of advanced age women undergoing in vitro fertilization/Intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET), and the effect on expession of L-Glutathione(GSH) in Follicular fluid (FF) and mitochondrial DNA( mtDNA ) copy number of granulosa cells. Methods:The present prospective randomised controlled study was conducted in 200 patients with advanced age women undergoing GnRH antagonist protocol. The treatment group (group A) consisted of 100 women who received N-acetylcysteine treatment from menstrual phase of the previous cycle for about 45 days using the GnRH antagonist protocol. The control group (group B) consisted of 100 women who received the same protocol without N-acetylcysteine. Gn doses, the number of oocyte received and high-quality blastocysts, and pregnancy outcomes were contrasted between two groups.Pregnancy outcomes included biochemical pregnancy rate,clinical pregnancy rate, embryo implantation rate, ectopic pregnancy rate,Multiple pregnancy rate and ongoing pregnancy rate. Follicular fluid (FF) was collected after oocyte gathered. Expression of the GSH in the FF was tested with enzymelinked immunosorbent assay (ELISA).The mtDNA copy number of the granulosa cells was messured using real-time PCR techniques. Results: Total doses of Gn in the NAC treatment group was less than those in the control group(2385.50±879.19 vs.2527.63±1170.33,P=0.047). Compared with the control, the number of high-quality blastocysts in NAC treatment increased significantly (1.82±2.12 vs. 1.43±1.58, p=0.014). Clinical pregnancy rates did not differ in both groups(all P＞0.05). At the same time, the GSH content in the FF differed significantly between the two groups (1.88±1.23 vs. 1.07±0.70, p=0.001).There was no significance about mtDNA copy number between the two grous (P=0.157) . Conclusion: A combination of NAC and Gn treatment is capable of improving the ovarian response to superovulation drugs in assisted reproductive technologies(ART）and also in aged populations. The addition of NAC during IVF can improves the quality of blastocysts in advanced age females. However, more clinical trials are required to be designed to confirm this conclusion in the future.